2018
DOI: 10.1038/s41598-018-31881-w
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial separation of catches in highly mixed fisheries

Abstract: Mixed fisheries are the dominant type of fishery worldwide. Overexploitation in mixed fisheries occurs when catches continue for available quota species while low quota species are discarded. As EU fisheries management moves to count all fish caught against quota (the “landing obligation”), the challenge is to catch available quota within new constraints, else lose productivity. A mechanism for decoupling exploitation of species caught together is spatial targeting, which remains challenging due to complex fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…This result is comparable to Khoukh and Maynou (), who found that full protection of an important nursery area in the Catalan coast would be equivalent, in terms of increased catches, to a reduction of 20% in fishing effort. These results confirm the difficulty of optimally managing several species simultaneously in mixed fisheries (Dolder, Thorson, & Minto, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result is comparable to Khoukh and Maynou (), who found that full protection of an important nursery area in the Catalan coast would be equivalent, in terms of increased catches, to a reduction of 20% in fishing effort. These results confirm the difficulty of optimally managing several species simultaneously in mixed fisheries (Dolder, Thorson, & Minto, ).…”
Section: Discussionsupporting
confidence: 81%
“…Fisheries management must ideally address the simultaneous optimisation of often conflicting biological, social and economic objectives. Co-viability analysis studies the evolution of dynamic systems under constraints (Oubraham & Zaccour, 2018) and has been applied to bioeconomic fisheries models (Gourguet et al, 2013;Maynou, 2014;Tserpes, Nikolioudakis, Maravelias, Carvalho, & Merino, 2016) to help identify the management strategies that ensure that a fishery is viable (under some conditions) simultaneously for two or more criteria. When strong or absolute co-viability (Baumgärtner & Quaas, 2007) cannot be obtained, the analysis allows, at least, for the ranking of different management measures in terms of biological, social or economic viability.…”
Section: Introductionmentioning
confidence: 99%
“…Dolder, Thorson, & Minto, 2018). Joint dynamic species distribution models (JDSDM), which estimate population density including the degree of spatial autocorrelation, account for covariation in density and productivity among multiple species and incorporate changes in spatial distribution for multiple species over time .…”
Section: Me Thodsmentioning
confidence: 99%
“…Specifically, the MICE-in-space model identifies the predicted mix of species encountered at any given location, thereby providing an estimate of likely technical interactions (e.g. Dolder, Thorson, & Minto, 2018).…”
Section: Me Thodsmentioning
confidence: 99%
“…The area accommodates a high diversity of marine species that support fisheries targeting different species assemblages from pelagic to demersal (Gerritsen and Lordan 2011;Martinez et al 2013;Mateo et al 2017;Dolder et al 2018). The mixed nature of these fisheries leads to high discard rates, especially in the mixed demersal trawl fishery where many species occupy similar habitats and display similar behaviours making it difficult to selectively fish for individual species.…”
Section: Introductionmentioning
confidence: 99%